2015
DOI: 10.1093/jnci/djv391
|View full text |Cite
|
Sign up to set email alerts
|

The Added Value of Analyzing Pooled Health-Related Quality of Life Data: A Review of the EORTC PROBE Initiative

Abstract: The use of existing pooled data shows that it is possible to learn about general aspects of cancer HRQOL and methodology. Our work shows that setting up international pooled datasets holds great promise for understanding patients' unmet psychosocial needs and calls for additional empirical investigation to improve clinical care and understand cancer through retrospective HRQOL analyses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 35 publications
0
26
0
Order By: Relevance
“…Unidimensional instruments or subscales measure the severity of perceived fatigue and tend to be short and easy-to-use. Also, they have the most robust psychometric data to support their use since they are widely used: the FACT and the EORTC QLQ-C30 have been used in over 10.000 patients [39, 40]. However, fatigue is a multidimensional concept involving mood disorders, anxiety, cognitive disorders and physical distress [5].…”
Section: Discussionmentioning
confidence: 99%
“…Unidimensional instruments or subscales measure the severity of perceived fatigue and tend to be short and easy-to-use. Also, they have the most robust psychometric data to support their use since they are widely used: the FACT and the EORTC QLQ-C30 have been used in over 10.000 patients [39, 40]. However, fatigue is a multidimensional concept involving mood disorders, anxiety, cognitive disorders and physical distress [5].…”
Section: Discussionmentioning
confidence: 99%
“…Building on the WHO model of health, HRQOL can be defined as a multidimensional concept that refers to an individual's usual or expected physical, emotional, and social well-being. Notably, such PROMs that assess this range of concepts are increasingly becoming emphasized in clinical trials and other areas of medicine (Atherton & Sloan, 2006;Leidy, Beusterien, Sullivan, Richner, & Muni, 2006;Zikos et al, 2016). Although organized as discrete domains, physical, emotional, and social well-being are likely interrelated.…”
Section: Health-related Quality-of-life Measures As Promsmentioning
confidence: 99%
“…Before further mandates around PROMs collection are established, a gap in the evidence base for routine collection of PROMs or PREMs in CKD clinical care, and/or for quality assurance needs to be addressed. Prior systematic reviews in other disease areas have shown mixed results with respect to improvement in patient outcomes or processes of care that can be achieved through regular measurement . The exception appears to be with the assessment of symptoms and subsequent targeted action to address them .…”
Section: Discussionmentioning
confidence: 99%
“…Prior systematic reviews in other disease areas have shown mixed results with respect to improvement in patient outcomes or processes of care that can be achieved through regular measurement. 27,28 The exception appears to be with the assessment of symptoms and subsequent targeted action to address them. 29 New evidence from oncology suggests that quality of life and survival benefits may be realized by addressing symptoms in a systematic way.…”
Section: Discussionmentioning
confidence: 99%